The Effect of Giving Hot-Packs on The Grade of Shivering in Post-Surgery Caesarean Section Patients at Grandmed Hospital Lubuk Pakam - Syara, Arfah May; Syatriawati (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Shivering after anesthesia is a recovery mechanism in the body due to negative side effects such as discomfort and pain due to stretching of the surgical scar, and increased muscle activity following increased oxygen demand. When a client experiences shivering, it is necessary to warm the body with heat therapy given to clients whose temperature is ? 36?C. A hot-pack is a closed package containing gel with a temperature of 40?C. The hot-pack will be given on the right and left inner arms for about 15 minutes. The type of research used is pre-experimental with one group Pre-test and Post-test design. The technique used in sampling in this study is non-probability sampling, in the form of Accidental sampling with a sample size of 20 respondents, while the instrument used in this study is an observation sheet. This study uses univariate and bivariate analysis. In this study, bivariate analysis was carried out using the Paired T-Test. Based on the Statistical Test conducted using the Paired Sample T-test method, the value obtained was p value 0.000 (? <0.05) which means Ho is rejected and Ha is accepted. This means that there is an Effect of Giving Hot-Packs on the Degree of Shivering in Post-Caesarean Section Patients at Grandmed Hospital Lubuk Pakam. This study concludes that giving hot-packs reacts to skin receptors and channels the temperature effect on body heat so that it can reduce shivering.